Running performance in Turkish professional football leagues: A comparative analysis of Süper Lig and 1st league teams in the 2022-2023 season - Bayrak, A.; Peker, C.; Bakum, A.; Heper, E. (Turkish Journal of Sport and Exercise, 2025)
This study aimed to compare specific running performance metrics of teams competing in the Turkish Football Federation`s 2022-2023 Süper Lig and First Division (1st Lig). The sample included teams that finished the season at the top, middle, and bottom of each league: Galatasaray (top), Kasimpasa FK (middle), and Ümraniyespor (bottom) from the Süper Lig, and Samsunspor (top), Bandirmaspor (middle), and Yeni Malatyaspor (bottom) from the 1st Lig. Data were collected using the OPTA analysis program and included total running distance, high-speed running distance, sprint distance, number of high-speed accelerations, sprint count, and maximum speed. SPSS version 26 was used for statistical analysis. One-way ANOVA and the Duncan post-hoc test were applied for intra-league comparisons, while independent t-tests were used for comparisons between leagues (p<0.05). Results showed that while total running distance did not differ significantly among 1st Lig teams, other variables showed significant differences (p<0.05). In the Süper Lig, total distance, high-speed distance, and high-speed accelerations were similar, but sprint-related metrics differed (p<0.05). Overall, Süper Lig teams displayed superior running performance compared to 1st Lig teams, and within each league, higher-ranked teams demonstrated better performance than those ranked lower.